2021
DOI: 10.1021/acsbiomaterials.1c00159
|View full text |Cite
|
Sign up to set email alerts
|

Polyplex-Loaded Hydrogels for Local Gene Delivery to Human Dermal Fibroblasts

Abstract: Impaired cutaneous healing, leading to chronic wounds, affects between 2 and 6% of the total population in most developed countries and it places a substantial burden on healthcare budgets. Current treatments involving antibiotic dressings and mechanical debridement are often not effective, causing severe pain, emotional distress and social isolation in patients for years or even decades, ultimately resulting in limb amputation. Alternatively, gene therapy (such as mRNA therapies) emerges as a viable option to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 65 publications
0
25
0
Order By: Relevance
“…This study demonstrated the effective delivery of the ASON to the wounded tissue . Gene therapy can also be achieved by loading the hydrogel with nucleic acid-loaded nanoparticles (e.g., liposomes, polyplexes) as cargo to further enhance mucosal gene delivery …”
Section: Applications In Inflammatory and Infectious Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…This study demonstrated the effective delivery of the ASON to the wounded tissue . Gene therapy can also be achieved by loading the hydrogel with nucleic acid-loaded nanoparticles (e.g., liposomes, polyplexes) as cargo to further enhance mucosal gene delivery …”
Section: Applications In Inflammatory and Infectious Diseasesmentioning
confidence: 99%
“…197 Gene therapy can also be achieved by loading the hydrogel with nucleic acidloaded nanoparticles (e.g., liposomes, polyplexes) as cargo to further enhance mucosal gene delivery. 198…”
Section: Mucosal Delivery Of Biologicsmentioning
confidence: 99%
“…Hydrogels can also be effective at binding to and protecting encapsulated cargo. For example, Oliva, Borros, and co-workers report a hydrogel-based wound healing patch containing mRNA-encapsulated nanoparticles . The hydrogel protected the genetic cargo from degradation and improved transfection.…”
Section: Applications Of Advanced Biomedical Hydrogelsmentioning
confidence: 99%
“…Scaffolds, such as hydrogels [ 2 , 10 ] and nanofibers [ 11 , 12 , 13 , 14 ], with nucleic acids, could be used for gene delivery as an alternative method to eliminate the above issues. These systems are capable of direct and sustained delivery of nucleic acids to cells and tissues [ 10 ]. In addition, these scaffolds have other advantages.…”
Section: Introductionmentioning
confidence: 99%
“…Second, local delivery using these scaffolds promotes tissue regeneration by supporting cell adhesion, proliferation, and migration. Third, these scaffolds can protect nucleic acids from extracellular or acidic environments [ 10 , 16 ].…”
Section: Introductionmentioning
confidence: 99%